2023
DOI: 10.1177/15353702231151976
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol alleviates neuronal damage via inhibiting inflammatory process against pilocarpine-induced status epilepticus

Abstract: Neuroinflammation is one of the most common pathological outcomes in various neurological diseases. A growing body of evidence suggests that neuroinflammation plays a pivotal role in the pathogenesis of epileptic seizures. Eugenol is the major phytoconstituent of essential oils extracted from several plants and possesses protective and anticonvulsant properties. However, it remains unclear whether eugenol exerts an anti-inflammatory effect to protect against severe neuronal damage induced by epileptic seizures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Furthermore, eugenol ameliorates silver nanoparticlesinduced nephrotoxicity (Aboelwafa et al, 2022) and hepatotoxicity in male rats, with parallel improvement of the histopathological alterations (Yousef et al, 2022). Moreover, it attenuates the neuro-inflammation outcomes in various neurological diseases (Zhu et al, 2023). The current results verified the mitigating roles of eugenol as an antioxidant phenolic agent, on γ-rays-induced acute renal destructive impacts, in line with the consideration that ROS are significant mediators of γ-rays-induced acute renal nephrotoxicity (El Bakary et al, 2022).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, eugenol ameliorates silver nanoparticlesinduced nephrotoxicity (Aboelwafa et al, 2022) and hepatotoxicity in male rats, with parallel improvement of the histopathological alterations (Yousef et al, 2022). Moreover, it attenuates the neuro-inflammation outcomes in various neurological diseases (Zhu et al, 2023). The current results verified the mitigating roles of eugenol as an antioxidant phenolic agent, on γ-rays-induced acute renal destructive impacts, in line with the consideration that ROS are significant mediators of γ-rays-induced acute renal nephrotoxicity (El Bakary et al, 2022).…”
Section: Discussionsupporting
confidence: 79%
“…It has been shown that eugenol, the primary phytoconstituent of essential oils, reduced apoptotic neuronal cell death induced by pilocarpine, mitigated both astrocytosis and microgliosis, attenuated the expression of IL-1β and TNFα, inhibited NF-κB activation, and the formation of the NLRP3 inflammasome following the onset of SE [176]. In a similar study, NLRP3 inflammasome components were activated upon lithium-pilocarpine induction in immature rats.…”
Section: Pilocarpine Modelmentioning
confidence: 79%
“…In fact, the potential effect of eugenol against Plasmodium falciparum with an impact on cerebral malaria in an experimental murine model were recently reported [ 43 ]. In fact, accumulating studies have shown the beneficial effects of eugenol under various neuropathological conditions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%